Opportunities and Challenges of Transitioning To a Green Economy In Regional Economic Development - ugli, Jumaniyazov; Ulugbekovich, Raxmatullayev; Otaxanovich, Xaitbayev; Yusupbayevich, Umarov (Indonesian Journal Publisher, 2025)
This article analyzes the opportunities and challenges of transitioning to a green economy in regional economic development. The main goals of a green economy are the efficient and sustainable use of natural resources, reduction of environmental risks, and ensuring economic growth. The article emphasizes the necessity of considering social, economic, and environmental factors at the regional level during the transition to a green economy. It also analyzes the impact of this transition on economic growth and sustainable development, as well as opportunities for job creation, improving energy efficiency, and waste reduction. However, several issues related to implementing this process are also discussed, including the lack of financial resources, difficulties in adopting technological innovations, development of local infrastructure, and insufficient political will. The article highlights the importance of transitioning to a green economy for regional economic development and suggests ways to overcome potential obstacles in implementing this process.